PENGEMBANGAN MULTIMEDIA BERBASIS APLIKASI KAHOOT PADA MATA PELAJARAN BAHASA INDONESIA TEMA BELAJAR BERWIRAUSAHA SISWA KELAS V SDN DRINGU - Sabrina Dwi Maulidia Putri; Didit Yulian Kasdriyanto; Faridahtul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the era of the Industrial Revolution 4.0, technological developments have an important role in education, including Indonesian language subjects. Teachers and students can utilize technological advances to create more interesting and enjoyable learning. However, the reality in the field is the lack of use of learning media that can make students active in learning, causing low levels of student motivation in Indonesian language subjects in the classroom. This research aims to produce a product in the form of multimedia based on the Kahoot application in Indonesian language subjects on the theme of learning entrepreneurship for grade V students at SDN Dringu. This research method uses a research and development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the product trial research show the level of feasibility with an average score of 94% with the product feasibility assessment criteria in the very feasible category. If described, the media expert gets a score of 96%, the material expert gets a score of 92%, and the learning practitioner gets a score of 94%. While the questionnaire results from student responses scored 90% with a very good category. The conclusion of the research and development of Kahoot application-based multimedia is an interesting and fun game-based digital media. Kahoot application-based multimedia can be used as a tool in Indonesian subjects on the theme of learning entrepreneurship when it will be studied by utilizing the features in the Kahoot application.